Open-Source Statistical Software: Revolutionising Health Research - Masood Ali Shaikh,; Syed Muhammad Mubeen, (Journal of the Pakistan Medical Association, 2025)
Data are everywhere, and medical and public healthresearch depends on making sense of it. This requiresutilisation of advanced statistical and geographicalinformation system (GIS) tools to glean insights from data,guide health and public policies, and promote healthsciences to reduce the global burden of morbidity andmortality. Proprietary statistical software programmes likeSAS, SPSS, and Stata, along with ArcGIS for mapping andspatial analysis, have dominated the statistical analysisfield for decades. The emergence of open-source softwarefor statistical analysis, such as R, Python, and Julia, as wellas spatial analysis software like QGIS, is challenging theseproprietary behemoths. These open-source softwaresolutions provide cutting-edge analytical capabilities atno financial cost, thereby democratising access to healthdata analysis and insights for improving the health ofpopulations globally. Continue...